REPRESENTASI SECRET HOMOSEXUAL DALAM FILM "BEBAS" (Analisis Semiotika Roland Barthes) - Muhammad Farhan Fachrezzy (2021)
Bebas is a 2019 Indonesian film directed by Riri Riza and produced by Miles Film, which was adapted from a Korean film entitled "Sunny". This comedy-drama film tells the story of the friendship of 6 people who call their group as geng bebas from high school until they became a grow up. Geng Bebas consist of 5 women, namely Kris, Vina, Jessica, Gina, and Suci, and 1 man, namely Jojo. Jojo himself became the representation of secret homosexuals in Indonesian cinema that year through implicitly constructed scenes. In conducting this research, the researcher uses Roland Barthes' semiotic analysis method to analyze the scenes where there are hints or meanings of homosexuality or homosexual secrets in the film, both verbally and non-verbally. The scenes were categorized and analyzed using the concepts of homosexual and secret homosexual and strengthened by the researcher through interviews with two respondents who identified themselves as secret homosexuals. Bebas, through its semiotics, provides an overview of what is experienced and happens in the real world for individuals, especially men, who identify themselves as secret homosexuals.